2018
DOI: 10.21037/mhealth.2018.06.01
|View full text |Cite
|
Sign up to set email alerts
|

Mental health apps in a college setting: openness, usage, and attitudes

Abstract: There is interest in, but limited usage, of MHAs among university students, providing evidence of MHAs as a potentially untapped treatment modality for this population. Further research could help assess how best to integrate this technology into the university and college mental health system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 28 publications
5
60
0
5
Order By: Relevance
“…The use of phone apps within mental health care is on the rise, with more people preferring to communicate in this manner [ 18 , 23 ]. However, 1 recent study surveyed college students and found that only 26% reported that they would use mental health apps, with the majority (81%) preferring to talk to a person [ 64 ]. It has also been suggested that digital apps can help reduce barriers to face-to-face help-seeking, such as stigma and discomfort about discussing one’s own mental health [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of phone apps within mental health care is on the rise, with more people preferring to communicate in this manner [ 18 , 23 ]. However, 1 recent study surveyed college students and found that only 26% reported that they would use mental health apps, with the majority (81%) preferring to talk to a person [ 64 ]. It has also been suggested that digital apps can help reduce barriers to face-to-face help-seeking, such as stigma and discomfort about discussing one’s own mental health [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…In one study, although a small number of students had used a mental health app, more than one-fourth were open to using an app. At the same time, students were largely unsure of whether mental health apps were evidence based and voiced concerns about the efficacy and impersonal nature of apps [ 5 ]. This suggests that acceptability is a key factor to investigate when researching mental health apps for college students; students may find apps with clear research evidence or apps tailored to their specific needs more acceptable.…”
Section: Introductionmentioning
confidence: 99%
“…College students and young adults are rarely without their phones, using them for several facets of their lives, generally through mobile apps. Some research suggests that college students would rather use in-person resources than web-based resources for mental health; however, college students are likely to use web-based resources because of their availability, convenience, and confidentiality [ 13 - 15 ]. Mobile apps for mental health services can provide users with additional benefits that seeking face-to-face help does not provide, such as its relatively low cost for care and the lack of stigma from seeking in-person treatment.…”
Section: Introductionmentioning
confidence: 99%
“…When examining college students’ openness and attitudes toward using mental health apps in a college setting, researchers found that 26.1% of college students were open to using mental health apps; however, only 7.3% had ever used such an app before [ 13 ]. The relatively low rate of mental health app adoption was attributed to participants having no current mental health needs, perceptions that mental health apps felt too impersonal, confidentiality concerns, and the utility of the apps [ 13 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation